Families' experiences of involvement in care planning in mental health services: an integrative literature review. Issue 6 (4th July 2017) - Doody, O.; Butler, M. P.; Lyons, R.; Newman, D.
Accessible summary: What is known on the subject?: Current policy advocates for the participation of family carers in care planning. Caring for a person with a mental illness requires a significant commitment from families to support their relative's recovery. What this paper adds to existing knowledge?: The evidence of family involvement in care planning is generally fraught with conflicting experiences related to different requirements between mental health professionals, families and service users. Confidentiality remains contentious at a practice level in terms of information sharing and decision‐making. There is a requirement and need for a shared understanding around care planning between families and mental health professionals. What are the implications for practice?: The provision of written information pertaining to families regarding confidentiality is required at service level. Educational workshops concerning care planning and treatment options should be provided for service users, families and mental health professionals. Further research into effective service‐wide strategies that explore with families how their engagement can be positively fostered in mental health services is warranted. Abstract: Introduction: Mental health service policy stipulates that family carers be involved in care planning. Aim: To identify families' experiences of care planning involvement in adult mental health services. Method: An integrative review where electronic databases and grey literature were searched for papers published between 01 January 2005 and 10 February 2016. Results: Fifteen papers met the inclusion criteria. Thematic analysis generated three themes: (1) families' experience of collaboration, (2) families' perceptions of professionals and (3) families' impressions of the care planning process. Collaborative decision‐making is not regularly experienced by families with an 'us' and 'them' divide, perpetuated by a lack of communication, confidentiality constraints and a claim of 'insider knowledge' of service users. When involved, families perceive care planning to be uncoordinated and that their lived experiences are not always appreciated. Discussion: Families need to be valued, empowered and engaged in care planning and the partnership distance be addressed. Accommodating the views of family, service user and professionals is preferable but not always possible. Our findings suggest that the key element for professionals is to value all 'insider knowledge' where possible. Implications for Practice: Services should develop written information on confidentiality for families and facilitate open communication concerning their involvement in care planning.